"CLINICAL IMPLICATIONS OF SUGAMMADEX AND OTHER MUSCLE RELAXANTS IN PATIENTS WITH HYPERCONTRACTION IN THE CRANIAL TERRITORY AND MASTICATORY MUSCLES. PART 3-DIAGNOSTIC AND TREATMENT, ORAL COMPLEX REHABILITION" - Ștefan Lucian Burlea; Doriana Agop Forna; Laura Elisabeta Checherita; Tudor Hamburda; Maria Antonela Beldiman; Vlad Proca; Larisa Tarevici; Bogdan Petru Bulancea (Romanian Journal of Oral Rehabilitation)
To improve therapeutic outcomes in elderly patients undergoing complex oral rehabilitation, further studies exploring the potential use of sugammadex in this context would be needed. At present, there is no evidence to support extending its use in the treatment of TMD.